The procedure dimension of an assessing model for the teachers in the preuniversity system of learning - TASCOVICI, Daliana Ecaterina; DRAGOMIR, Robert Gabriel (Annals of Spiru Haret University. Economic Series, 2010)
The paper is part of an ample research which proposes to fundament theoretically, methodologically and procedurally an assessing model for the teachers in the pre university system of learning. The purpose of the present paper consists in presenting the procedure dimension of the above mentioned assessing model.